A Review of Microreactors for Process Intensification - Crizha Ann Bugay; Mae Czarella Caballas; Steven Brian Mercado; Jason Franco Rubio; Patricia Kayla Serote; Patrick Norman Villarte; Rugi Vicente C. Rubi (Engineering Proceedings)
Microreactors for process intensification transform chemical synthesis, providing precise control over reactions in compact devices and enhancing efficiency. This review article explores their application in chemical synthesis, emphasizing advantages in mixing, temperature control, and heat transfer. It delves into fundamental aspects, addressing challenges in design, operation, material selection, and scaling. Fundamental microreactor design principles involve scaling strategies such as internal and external numbering up, geometric similarity, and continuous pressure drop procedures. Materials like silicon, steel, and polymers, particularly polydimethylsiloxane (PDMS), play a crucial role in microreactor construction. Fabrication techniques, including microfabrication, are essential for creating complex designs and ensuring reliability. This review addresses challenges and research gaps while showcasing the versatility of microreactors. Challenges include automation, integration, finding optimal configurations, process optimization, and cost analyses. Overcoming these challenges is crucial for widespread adoption in industries like pharmaceuticals and petrochemicals. The future for microreactors will revolve around recent advancements, collaboration between academia and industry, and the integration of automation and sensors. This positions microreactors as key players in revolutionizing chemical production, with potential applications in fuel cells, mini-chemical plants, and next-generation catalysts. Therefore, it is of the utmost importance to address the current challenges and advance research related to this study in order to solidify their role in shaping the future of chemical engineering.